2015
DOI: 10.1155/2015/524754
|View full text |Cite
|
Sign up to set email alerts
|

Whole Exome Sequencing Identifies a Novel and a Recurrent Mutation inBBS2Gene in a Family with Bardet-Biedl Syndrome

Abstract: Bardet-Biedl syndrome (BBS) is a rare autosomal recessive disorder known to be caused by mutations in at least 19 BBS genes. We report the genetic analysis of a patient with indisputable features of BBS including cardinal features such as postaxial polydactyly, retinitis pigmentosa, obesity, and kidney failure. Taking advantage of next-generation sequencing technology, we applied whole exome sequencing (WES) with Sanger direct sequencing to the proband and her unaffected mother. A pair of heterozygous nonsense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…The literature search was performed according to the protocol preregistered in Prospero (CRD42018096099) and it followed the PRISMA guidelines whenever applicable (Table S1 and Figure S1). In total, we identified 85 relevant studies (Abu Safieh et al, ; Agha et al, ; Ajmal et al, ; Al‐Hamed et al, ; Alazami et al, ; Aldahmesh et al, ; Azari et al, ; Badano, ; Baker et al, ; Bee, Chawla, & Zhao, ; Bennouna‐Greene et al, ; Billingsley et al, ; Billingsley, Vincent, Deveault, & Heon, ; Branfield Day et al, ; Braun et al, ; Bujakowska et al, ; Castro‐Sanchez et al, ; Chaki et al, ; Chul Yoon et al, ; Cox et al, ; Davies, ; Deveault et al, ; Ece Solmaz et al, ; Esposito et al, ; Estrada‐Cuzcano, Koenekoop, et al, ; Estrada‐Cuzcano, Neveling, et al, ; Fan et al, ; Fattahi et al, ; Fedick et al, ; Frank et al, ; Gerth, Zawadzki, Werner, & Heon, ; Ghadami et al, ; González‐del Pozo et al, ; Harville et al, ; Heon et al, ; Hjortshoj, Gronskov, Brondum‐Nielsen, & Rosenberg, ; Hjortshoj et al, ; Hulleman et al, ; Iannaccone et al, ; Innes et al, ; Iurian, Arts, Brunner, & Fintina, ; Janssen et al, ; Kamme, Mayer, Strom, Andréasson, & Weisschuh, ; Katsanis et al, ; Katsanis et al, ; Kerr, Bhan, & Héon, ; A. O. Khan, Decker, Bachmann, Bolz, & Bergmann, ; S. Khan et al, , S. A. Khan et al, ; Laurier et al, ; Leitch et al, ; Lim et al, ; Lindstrand et al, ; Lindstrand et al, ; M'Hamdi et al, ; Maria et al,…”
Section: Resultsmentioning
confidence: 99%
“…The literature search was performed according to the protocol preregistered in Prospero (CRD42018096099) and it followed the PRISMA guidelines whenever applicable (Table S1 and Figure S1). In total, we identified 85 relevant studies (Abu Safieh et al, ; Agha et al, ; Ajmal et al, ; Al‐Hamed et al, ; Alazami et al, ; Aldahmesh et al, ; Azari et al, ; Badano, ; Baker et al, ; Bee, Chawla, & Zhao, ; Bennouna‐Greene et al, ; Billingsley et al, ; Billingsley, Vincent, Deveault, & Heon, ; Branfield Day et al, ; Braun et al, ; Bujakowska et al, ; Castro‐Sanchez et al, ; Chaki et al, ; Chul Yoon et al, ; Cox et al, ; Davies, ; Deveault et al, ; Ece Solmaz et al, ; Esposito et al, ; Estrada‐Cuzcano, Koenekoop, et al, ; Estrada‐Cuzcano, Neveling, et al, ; Fan et al, ; Fattahi et al, ; Fedick et al, ; Frank et al, ; Gerth, Zawadzki, Werner, & Heon, ; Ghadami et al, ; González‐del Pozo et al, ; Harville et al, ; Heon et al, ; Hjortshoj, Gronskov, Brondum‐Nielsen, & Rosenberg, ; Hjortshoj et al, ; Hulleman et al, ; Iannaccone et al, ; Innes et al, ; Iurian, Arts, Brunner, & Fintina, ; Janssen et al, ; Kamme, Mayer, Strom, Andréasson, & Weisschuh, ; Katsanis et al, ; Katsanis et al, ; Kerr, Bhan, & Héon, ; A. O. Khan, Decker, Bachmann, Bolz, & Bergmann, ; S. Khan et al, , S. A. Khan et al, ; Laurier et al, ; Leitch et al, ; Lim et al, ; Lindstrand et al, ; Lindstrand et al, ; M'Hamdi et al, ; Maria et al,…”
Section: Resultsmentioning
confidence: 99%
“…WES limits the capture and sequencing to gene exons, and is well suited for rare Mendelian disorders. Bee et al utilized this approach to identify a novel mutation (p.Y644X) in the BBS2 gene (74).…”
Section: Gene Identification Techniquesmentioning
confidence: 99%
“…However, difficulty in distinguishing between causal and coincidental obesity in unique cases necessitates replication of these results in additional patients. WES has also discovered novel mutations and/or structural variants for syndromic obesity in previously implicated genes and revealed clinical heterogeneity in several obesity syndromes . For example, in a study of individuals with atypical Alström syndrome, novel ALMS1 mutations were identified using WES secondary to a negative classical genetic test of ALMS1 mutational hotspots .…”
Section: Established Strategiesmentioning
confidence: 99%